2008
DOI: 10.1136/ard.2008.089557
|View full text |Cite
|
Sign up to set email alerts
|

Elevated synovial expression of triggering receptor expressed on myeloid cells 1 in patients with septic arthritis or rheumatoid arthritis

Abstract: Synovial TREM-1 expression is increased in septic arthritis and RA. In patients with acute inflammatory arthritis, elevated SF sTREM-1 levels may point the clinician to a diagnosis of septic arthritis or RA. In RA patients, targeting TREM-1 may have therapeutic benefits by reducing local proinflammatory cytokine and chemokine release.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
69
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 22 publications
8
69
0
1
Order By: Relevance
“…Previously published researchers showed that sTREM‐1 levels are centrally involved in acute microbial inflammation and are a crucial mediator of septic shock; only 19% of healthy controls had detectable sTREM‐1 9, 10. However, the role of sTREM‐1 is subject to intensive research in various noninfectious diseases, such as heart surgery, cardiac arrest, anti–neutrophil cytoplasmic antibody–associated vasculitis, and rheumatoid arthritis 30, 31, 32, 33, 34, 35. Therefore, it is reasonable to propose that elevated sTREM‐1 in the serum could be derived from activated monocytes/macrophages in atherosclerotic plaque or neutrophils accumulated in the injured myocardium after AMI.…”
Section: Discussionmentioning
confidence: 99%
“…Previously published researchers showed that sTREM‐1 levels are centrally involved in acute microbial inflammation and are a crucial mediator of septic shock; only 19% of healthy controls had detectable sTREM‐1 9, 10. However, the role of sTREM‐1 is subject to intensive research in various noninfectious diseases, such as heart surgery, cardiac arrest, anti–neutrophil cytoplasmic antibody–associated vasculitis, and rheumatoid arthritis 30, 31, 32, 33, 34, 35. Therefore, it is reasonable to propose that elevated sTREM‐1 in the serum could be derived from activated monocytes/macrophages in atherosclerotic plaque or neutrophils accumulated in the injured myocardium after AMI.…”
Section: Discussionmentioning
confidence: 99%
“…Individual microbial components, such as lipopolysaccharide (LPS) and peptidoglycan, can cause up-regulation of cell surface-localized TREM-1 by monocytes, as well as release in its soluble (s)TREM-1 form (Begum et al, 2004;Gibot et al, 2004b;Gomez-Pina et al, 2007;Murakami et al, 2007;Ramanathan et al, 2005;Zeng et al, 2007). The sTREM-1 appears to be released during the course of infection, and may well be a particularly useful marker of systemic inflammation, as demonstrated in systemic sepsis, septic arthritis, pneumonia (Collins et al, 2009;Gibot et al, 2005;Gibot et al, 2004a;Gibot et al, 2004c;Knapp et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This has been well demonstrated in systemic sepsis (Gibot et al, 2004a;Gibot et al, 2004b;Su et al, 2012), arthritis (Collins et al, 2009;Murakami et al, 2007), pulmonary infections (Ruiz-Gonzalez et al, 2011), pancreatitis (Yasuda et al, 2008) and inflammatory bowel disease (Park et al, 2009). sTREM-1 is a biomarker that can easily be measured in biological fluids (Skogstrand et al, 2005).…”
Section: The Engagement Of Trem-1 In In Vivomentioning
confidence: 99%